Bystanders to Sexual Violence: Findings From a National Sample of Sexual and Gender Diverse Adolescents - Banyard, Victoria (Journal of interpersonal violence, 2025)
Mobilizing bystanders to prevent sexual violence is an increasingly popular prevention strategy. While research has identified characteristics related to opportunity and actions around helping, a more nuanced understanding of how helping behavior and its modifiable levers may differ for youth of various genders is needed. The current study examined bystander-helping behaviors in sexual violence situations in a national, social media-recruited sample of adolescents 14 to 16 years of age. Measures of opportunity and self-reported actions were included in an online survey along with items assessing attitudes related to violence and helping. Given that prevention programs may work differently for cisgender, transgender, and nonbinary young people, between-group differences in amount of opportunity and helping behaviors were examined. Further, we examined correlates of opportunities to help as well as helping behaviors within each group. Overall, few attitude and personal experience characteristics consistently predicted opportunities and behaviors across groups. Group differences that emerged, such as the association between attitudes supportive of rape and lower helping for cisgender but not trans or nonbinary youth, support attending to these group differences in both basic and intervention research to inform tailoring of prevention programs.